Harmonising knowledge for safer materials via the “NanoCommons” Knowledge Base - Maier, Dieter; Exner, Thomas E.; Papadiamantis, Anastasios G.; Ammar, Ammar; Tsoumanis, Andreas; Doganis, Philip; Rouse, Ian; Slater, Luke T.; Gkoutos, Georgios V.; Jeliazkova, Nina; Ilgenfritz, Hilmar; Ziegler, Martin; et al. (Frontiers in Physics, 2023)
In mediaeval Europe, the term "commons" described the way that communities managed land that was held 'in common' and provided a clear set of rules for how this "common land" was used and developed by, and for, the community. Similarly, as we move towards an increasingly knowledge-based society where data is the new oil, new approaches to sharing and jointly owning publicly funded research data are needed to maximise its added value. Such common management approaches will extend the data's useful life and facilitate its reuse for a range of additional purposes, from modelling, to meta-analysis to regulatory risk assessment as examples relevant to nanosafety data. This "commons" approach to nanosafety data and nanoinformatics infrastructure provision, co-development, and maintenance is at the heart of the "NanoCommons" project and underpins its post-funding transition to providing a basis on which other initiatives and projects can build. The present paper summarises part of the NanoCommons infrastructure called the NanoCommons Knowledge Base. It provides interoperability for nanosafety data sources and tools, on both semantic and technical levels. The NanoCommons Knowledge Base connects knowledge and provides both programmatic (via an Application Programming Interface, API) and a user-friendly graphical interface to enable (and democratise) access to state of the art tools for nanomaterials (NMs) safety prediction, NMs design for safety and sustainability, and NMs risk assessment, as well. In addition, the standards and interfaces for interoperability, e.g., file templates to contribute data to the NanoCommons, are described, and a snapshot of the range and breadth of nanoinformatics tools and models that have already been integrated are presented Finally, we demonstrate how the NanoCommons Knowledge Base can support users in the FAIRification of their experimental workflows and how the NanoCommons Knowledge Base itself has progressed towards richer compliance with the FAIR principles.